The Digital Analysis of the Dark Figures of Crime During the 2023 Earthquake Disaster Period in Türkiye - Küpeli, Ceren; Türkmen, Zeynep; Bozkurt, Musa (The Bulletin of Legal Medicine, 2025)
Objective: The aim of this study was to gain insights into crimes occurring in the dark figure during the earthquake disasters that took place in Turkey in 2023, measuring magnitudes of 7.4 and 7.6, within the context of post-disaster intervention and crime prevention efforts. Methods: A qualitative digital analysis was conducted, targeting crimes committed during the disaster period that remained largely undocumented. Data were gathered from the social media platform X (formerly Twitter), using keyword combinations like “earthquake debris” and various crime-related hashtags from 2023. Additionally, fake donation websites were examined through USOM data, especially those exploiting individuals aiming to support victims. Results: The crimes most frequently shared with hashtags on X were looting (65%) and theft (29%) against earthquake victims. Regarding individuals sending financial aid, the dominant crime identified was qualified fraud, primarily via fake donation platforms. Conclusion: In post-disaster contexts, strengthening both physical and cyber security mechanisms is essential. Quick access restrictions on fraudulent websites, supported by deep learning–based verification of shared digital content, should be implemented. Furthermore, launching ex officio investigations—especially into looting, theft, and fraud—and forming proactive crime prevention policies are critical. These steps could curb criminal activity and mitigate the societal perception of “impunity” following disasters.